Pentingnya Pengenalan Akan Musik dan Bahasa Inggris di Jaman Milenial Sekarang - Kamaluddin Galingging; Sheren R.G. Waruwu; Kartika E. Aritonang; Widya Septiana; Sempurna Sihombing; Miranda W. Padang (Jurnal Visi Pengabdian Kepada Masyarakat, 2022)
The Aims of the Thematic Field Practice (PLT) which carried out by students of the music arts study program and English literature study program at HKBP Nommensen University in Dataran Tinggi Village, East Binjai, Binjai City is to improve children's abilities in music and English. Lecturers together with students developing and applying knowledge and skills in real life on the field and in the community, so the students would be able to develop not only in the scope of campus but also in the outside community. The benefits to the community, especially children, are the increasing and insight of knowledge gained outside of the school and successfully increase in knowledge both theoretically and practically in terms of music and English. The method used was the training method and conducting interviews with local residents, namely the residents who provide a place to conduct music and English training.